Humoral Immunity Profiling to Pandemic and Bat‐Derived Coronavirus Variants: A Geographical Comparison - Parinaz Fathi; Andrea Lucia Alfonso; Christina Yek; Zoe Putman; Matthew Drew; Dominic Esposito; Irfan Zaidi; Sophana Chea; Sokna Ly; Rathanak Sath; Chanthap Lon; Huch Chea; et al. (Advanced Science)
Abstract Dynamic pathogen exposure may impact the immunological response to SARS‐CoV‐2 (SCV2). One potential explanation for the lack of severe SCV2‐related morbidity and mortality in Southeast Asia is prior exposure to related betacoronaviruses. Recent discoveries of SCV2‐related betacoronaviruses from horseshoe bats (Rhinolophus sinicus) in Thailand, Laos, and Cambodia suggest the potential for bat‐to‐human spillover exposures in the region. In this work, serum antibodies to protein constructs from SCV2 and a representative bat coronavirus isolated in Cambodia (RshSTT182) are measured in pre‐pandemic Cambodian human sera using ELISA assays. Of 293 Cambodian samples tested (N = 131 with acute malaria, n = 162 with acute undifferentiated febrile illness), 32 (10.9%) are seropositive for SCV2 based on established Spike and receptor‐binding domain (RBD) cutoffs. Within SCV2 seropositive samples, 16 (50%) have higher antibody levels to antigens from the representative virus RshSTT182 versus SCV2 antigens; competitive binding ELISA assays demonstrate inhibition of reactivity to SCV2 Spike after pre‐incubation with RshSTT182 Spike. Surrogate virus neutralization tests demonstrate that 8/30 (26.7%) SCV2 ELISA positive pre‐pandemic Cambodian samples have neutralizing activity against SCV2, while 14/30 (46.7%) have activity against other SCV2‐related betacoronaviruses. These data suggest that exposure to related betacoronaviruses may elicit cross‐reactive immunity to SCV2 prior to the global pandemic.